The influence of explosive power on the performance of an elite swimmer in 25 and 50 metre pools - Baumrtová, S.; Jebavý, R.; Hojka, V. (AUC Kinanthropologica, 2017)
Each swimming stroke, and each distance, requires a different approach to strength training. For sprinters in swimming the most essential part is explosive power. The goal of this case study was to find out how explosive training can influence the performance in both long course and short course meters swimming pools. This study was conducted with the cooperation of an elite swimmer over a time period of 6 years. Tests were performed twice a year (June and November) during the years of 2010-2016. The Myotest device was used to measure countermovement jump height. Swimming performance was evaluated by FINA points in the swimmer`s three main disciplines. ANOVA, Cohen`s d and regression equation were used for statistical analysis. The results showed that explosive power does not influence performance in the 50m swimming pool (p = 0.25; r2 = 0.08). However the performance in the 25m pool is directly linked to the level of explosive power of the lower limbs (p < 0.001; r2 = 0.85). The results of the swimmer in the 25m pool are closely related to the level of explosive power of the lower limbs. Performance in the 50m pool might not be affected by level of lower limb power.